Real-world clinical outcomes of meropenem/vaborbactam for treatment of carbapenem-resistant Enterobacterales infections - Helen L. Zhang (Elsevier, 2021)
ABSTRACT: Objectives: Real-world data regarding the effectiveness of meropenem/vaborbactam (MVB) in the treatment of carbapenem-resistant Enterobacterales (CRE) infections remain limited. In this retrospective case series, we describe the outcomes of patients who received MVB for serious CRE infections. Methods: This study included adult patients with MVB-susceptible CRE infection who received ≥48 h of MVB. Clinical and microbiological outcomes were ascertained via chart review. Results: Among 15 patients with CRE infection who were treated with MVB, 9 (60.0%) had a positive clinical response. Among five patients with CRE bone and joint infection, three (60.0%) experienced a positive clinical response. One patient developed a microbiologically confirmed recurrent CRE infection and one patient developed Clostridioides difficile infection. Conclusion: MVB was well tolerated and effective for the majority of patients in this case series.